An Efficient and One Spot Synthesis of Silica Supported Synthesis of Fluorinated 1,3,4-Thiadiazole Derivative Under Microwave Irradiation - Bharat K Dhotre; Bhagwan Singh Dobhalb; Santosh Raut; Amol Kalea; Pathan Mohd Arif (To Chemistry Journal, 2020)
An efficient and one pot reaction of fluorinated 1,3,4-Thiadiazole derivatives  was synthesis by fluorinated  aromatic carboxylic with thiosemicabazide in the presence of phosphorus oxychloride as a catalyst under Microwave irradiation with silica supported. The synthesis compound was characterized by 1H NMR, IR, and mass spectroscopic techniques. The present approach offers the advantages such as short reaction time, simplicity of the workup procedure, low cost and mild reaction condition.